Hubungan Variabel Demografi Dengan Perilaku Pembelian Impulsif Yang Dimoderasi Kepemilikan Kartu Kredit di Kota Denpasar - Sapitri, Ni Luh Gede Agis; Suprapti, Ni Wayan Sri (E-Jurnal Manajemen, 2014)
This Research aims to determine the relationship of gender, age, education, and income on impulsive buying are moderated credit card ownership. The study sample consisted of 120 consumers who frequently shop at a Matahari Duta Plaza and Ramayana mall in Denpasar. Half of the sample is the consumers who have a credit card, the rest do not have a credit card. The data were processed using regression analysis MRA (Moderated Regresion Analysis). The results of the data analysis showed that demographic variables are: gender, age, education, and income affect the simultaneous impulse purchases. Partially, gender, age, education, and credit card ownership a significant effect on impulsive purchases, while income does not significantly influence impulsive buying. Credit card ownership is significantly moderate the relationship of age and education with impulsive purchases, while gender relationships and revenues are not moderated by impulsive buying credit card ownership. Keywords : demographic variables, ownership credit card, impulsive buying.